2004
DOI: 10.1002/hed.10364
|View full text |Cite
|
Sign up to set email alerts
|

Single‐stage surgical repair of benign laryngotracheal stenosis in adults

Abstract: Benign laryngotracheal stenosis in the adult patient can be repaired successfully using a strategy of two single-stage surgical procedures. All patients had good or satisfactory functional results. A multidisciplinary approach was essential to achieve these good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…While the above referenced studies were mainly focused on "surgical success" (i.e., recurrence of stenosis, successful decannulation, reintervention rates), various authors have advocated that functional outcome parameters, such as pulmonary-, voice-, and swallowing-related functions, are equally as important in defining treatment success (8). However, few studies have published these patient-reported functional outcomes after tracheal surgery in adults (3).…”
Section: Introductionmentioning
confidence: 99%
“…While the above referenced studies were mainly focused on "surgical success" (i.e., recurrence of stenosis, successful decannulation, reintervention rates), various authors have advocated that functional outcome parameters, such as pulmonary-, voice-, and swallowing-related functions, are equally as important in defining treatment success (8). However, few studies have published these patient-reported functional outcomes after tracheal surgery in adults (3).…”
Section: Introductionmentioning
confidence: 99%
“…Other etiologies include Wegener granulomatosis, chemical injury, and gastroesophageal reflux disease. 1,2 Instrumentation of the trachea is by far the predominant cause of LTS in adults, with multiple series reporting intubation or tracheotomy as causes in more than 80% of patients. 3,4 The length, location, and severity of stenosis must all be considered in the treatment of LTS.…”
mentioning
confidence: 99%
“…[6][7][8] However, treatment of longsegment stenoses, typically beyond 6 tracheal rings, and stenoses that extend high within the larynx has limited success with primary resection. 1 In such challenging cases, staged LTP has been suggested to produce high decannulation rates. Laryngotracheoplasty is a general term encompassing wide ranges of surgical techniques and protocols.…”
mentioning
confidence: 99%
“…Surgical resection remains the standard of care of benign tracheal stenosis (2,19). However, many patients especially after prolonged intubation are not candidates for tracheal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection is the standard of care in the repair of these cases (2,3), many patients however are unable to medically tolerate a surgical procedure. In those cases, a combination of local therapy including laser ablation of granulation tissue and manual dilation and metallic stenting can be used to provide a palliative effect (4e6).…”
Section: Introductionmentioning
confidence: 99%